A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2017)
The Barsine obsoleta species-group is reviewed. A new species, Barsine fossi Volynkin & Černý, sp. nov. is described from Vietnam. A new combination is established: Barsine obsoleta (Reich, 1937), comb. nov. The neotype is designated for Miltochrista gratiosa f. obsoleta Reich, 1937. Diagnoses for B. obsoleta and B. callorufa Wu et al., 2013 are given. Adults, male and female genitalia of the species reviewed and externally close species are illustrated.